Pregnant women infected with Zika virus show higher viral load and immunoregulatory cytokines profile with CXCL10 increase - Camacho Zavala, Elizabeth; Santacruz-Tinoco, Clara; Muñoz, Esteban; Chacón-Salinas, Rommel; Salazar-Sanchez, Ma Isabel; Grajales, Concepción; González-Ibarra, Joaquin; Borja-Aburto, Victor Hugo; Jänisch, Thomas; Gonzalez-Bonilla, Cesar R. (Viruses, 2021)
Background: Zika virus (ZIKV) infection during pregnancy usually shows only mild symptoms and is frequently subclinical. However, it can be vertically transmitted to the fetus, causing microcephaly and other congenital defects. During pregnancy, the immune environment modifications can alter the response to viruses in general and ZIKV in particular. Objective: To describe the role of pregnancy in the systemic pro- and anti-inflammatory response during symptomatic ZIKV infection. Materials and Methods: A multiplex assay was used to measure 25 cytokines, chemokines, and receptors in 110 serum samples from pregnant and nonpregnant women with and without ZIKV infection with and without symptoms. Samples were collected through an epidemiological surveillance system. Results: Samples from pregnant women with ZIKV infection showed a higher viral load but had similar profiles of inflammatory markers as compared with nonpregnant infected women, except for CXCL10 that was higher in infected pregnant women. Notably, the presence of ZIKV in pregnancy favored a regulatory profile by significantly increasing anti-inflammatory cytokines such as interleukin (IL)-10, receptors IL-1RA, and IL-2R, but only those pro-inflammatory cytokines such as IL-6, interferon (IFN)-α, IFN-γ and IL-17 that are essential for the antiviral response. Interestingly, there were no differences between symptomatic and weakly symptomatic ZIKV-infected groups. Conclusion: Our results revealed a systemic anti-inflammatory cytokine and chemokine profile that could participate in the control of the virus. The anti-inflammatory response in pregnant women infected with ZIKA was characterized by high CXCL10, a cytokine that has been correlated with congenital malformations.
Gesehen am 24.02.2021